1989
DOI: 10.1017/s003118200006145x
|View full text |Cite
|
Sign up to set email alerts
|

Chloroquine containing liposomes in the chemotherapy of murine malaria

Abstract: In this study, the advantage of the use of chloroquine (CQ) containing liposomes (lipCQ) over free CQ in the chemotherapy of murine malaria (Plasmodium berghei) was demonstrated. The maximum permissible dose per intraperitoneal injection was 0.8 and 10 mg for CQ and lipCQ, respectively. An increase in therapeutic and prophylactic efficacy of lipCQ in comparison with free CQ at a 0.8 mg CQ dose level was found. It was possible to obtain 100% efficacy (injection at day 5 after infection; parasitaemia 4-8%) with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 18 publications
1
17
0
Order By: Relevance
“…Liposomes containing glycolipids with terminal galactose or glucose on the surface when injected into Plasmodium berghei sporozoite-infected mice prevented the appearance of asexual stages and hepatic infection (28). To overcome mild drug resistance, liposomes were used to deliver chloroquine for the treatment of CQ-resistant malaria (29). Liposomes bearing infected erythrocyte-specific antibodies have been used for the targeted delivery of chloroquine (30).…”
mentioning
confidence: 99%
“…Liposomes containing glycolipids with terminal galactose or glucose on the surface when injected into Plasmodium berghei sporozoite-infected mice prevented the appearance of asexual stages and hepatic infection (28). To overcome mild drug resistance, liposomes were used to deliver chloroquine for the treatment of CQ-resistant malaria (29). Liposomes bearing infected erythrocyte-specific antibodies have been used for the targeted delivery of chloroquine (30).…”
mentioning
confidence: 99%
“…This could indeed be the case, since delivery of CHQ in MAb F 10 -Lip should help to concentrate the drug in infected cells not only by the selective recognition of these cells but also by the ability of liposomes to deliver several drug molecules at a time to the target cells. Peeters et al (12) have shown that encapsulation of CHQ in liposomes (nontargeted) increases not only the maximal tolerable dose from 0.8 to 10 mg of CHQ per animal when given i.p. but also the effectiveness of the drug against both the CHQsusceptible and CHQ-resistant P. berghei infections.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies have shown that encapsulation of the antimalarial drug chloroquine (CHQ) in liposomes bearing antierythrocyte antibody on their surfaces markedly increases its efficacy against both CHQ-susceptible and CHQresistant Plasmodium berghei infections in mice (1,2). Also, Peeters et al (12) have reported that liposomization of CHQ increases not only its maximal tolerable dose but also its efficacy against the CHQ-resistant malarial infections. To further explore the possibility of using liposomized CHQ in the treatment of CHQ-resistant malaria, we examined the antimalarial activity of this drug after its encapsulation in liposomes bearing P. berghei-infected mouse erythrocyte-specific antibody on their surfaces.…”
mentioning
confidence: 99%
“…AmBisome | was also used for the treatment of visceral leishmaniasis in AIDS patients unresponsive to antimonial compounds and appeared to be effective for treatment and secondary prophylaxis [1 3 14]. In animal models of malaria (Plasmodium bergheO, the infection was successfully treated with liposome-encapsulated chloroquine even when the infectious organism was resistant to the free agent [15]. This could be ascribed to sustained release of chloroquine from the intraperitoneally injected liposomes.…”
Section: Liposome-mediated Delivery Of Antimicrobial Agentsmentioning
confidence: 99%